Confessione e biografia: per un avvenire fondato nella storia. Note a partire da Jacques Derrida e Jean-Luc Marion - Peruzzotti, Francesca (ETHICS IN PROGRESS, 2017)
This paper aims to draw a connection between Jacques Derrida and Jean-Luc Marion in regard to the role of negative theology. This scrutiny shows meaningful contributions of the Authors to a new definition of subjectivity in a post-metaphysical age, and their consideration about which possibilities are still open for a non-predetermined history given outside of the presence domain. The future is neither a totalisation of history by its end, nor a simple continuation of the present. It is an eschatological event, where the relationship with the other plays a crucial role for the self-constitution. Such an interlacement is generated by the confession, where the link between past and future is not causally determined, but instead it is self-witness, as in Augustine’s masterpiece, essential reference for both the Authors